Effect of the national business system on the disclosure of greenhouse gases emissions: multi-country evidence - Pinheiro, Alan Bandeira; Sampaio, Thicia Stela Lima; Mazzo, Gabriel Gusso; Carraro, Wendy Beatriz Witt Haddad; Ribeiro, Cintia de Melo de Albuquerque (Revista de Administração da UFSM, 2024)
Methodology: Institutional Theory and the National Business System approach were used to propose the research hypotheses. The work evaluated 1,072 companies from the 10 largest economies in the world, using econometric models and statistical analysis. Purpose: Investigate the effect of the national business system on the disclosure of greenhouse gases by companies from the largest economies in the world. Findings: The results indicate that institutional factors, such as the political, financial and cultural systems affect the disclosure of greenhouse gases. Thus, institutional pressure from countries can determine the environmental performance of their firms. However, the results showed that the country’s level of development is not an explanatory variable for the disclosure of atmospheric emissions. Practical implications: The research presents the impact of formal and informal institutions on the disclosure practices of companies, suggesting that policy makers could influence it by strengthening certain institutional aspects. Originality/Value: Although there is an increasing volume of research on the disclosure of corporate social responsibility, few studies are dedicated to comparing the disclosure of greenhouse gases in the light of the national business system.